(3CUM eWdhH hNjQ eMHhH aj Yde GdUfGYIs - (3GdHQgGfj GdeUQj GdMfaj GdENTjOj, YHO GdeLjO Hf jhfS, cGf MjG (B435 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdEfSGf Efj PGcQ aj gPG GdLeY GdhVjf ef Yde Gdjbjf eeG CdaJ hUfaJg aj MjGI CSJGPj CSO Hf GdaQGJ GdHZOGOj QMe Gddg KQGg heJYg aj OGQ cQGeJg HQDjGg s
(3BNQgG (B:s
(3UaI ejRGfjg jDNP bSe HQGf eQjN heKdg Ydef jbjS GdYde KdGKI CbSGe hjSMb GdeQjN HbSe hjOeS djdI Ke jNQL hjSMb HGdbSe GdKGfj hjOS Ke jSMb HGdbSe GdKGdK Je hceds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\311s
(3EjVGM Gdecfhf (B1\89s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs